The development of e-module optical physics instruments based on Creative Problem Solving (CPS) for improving high school students' digital literacy - Nuraeni, Ayuni; Rosana, Dadan (Education and Development Research, 2023)
The accelerating development of digital technology has shaped a rapidly evolving information landscape, significantly impacting the realm of education. The integration of digital technology in education necessitates a positive outlook and a strong digital literacy. The research adopts a Research and Development (R&D) approach and employs the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model for development. Data collection tools in this study include observation sheets, expert validation sheets, student response questionnaires, and digital literacy tests. The data analysis combines qualitative and quantitative techniques, including a t-test. The findings of this research indicate that the utilization of e-modules based on CPS only succeeded in enhancing the indicators of communication skills through digital media and the responsible and positive use of digital media, among all the digital literacy indicators.